CONDITIONS OF PARAMETRIC FEASIBILITYFOR AUTOMATED SYNTHESIS OF MECHANICALASSEMBLY ROBOTIC TECHNOLOGIES - Kyrylovych, V. (Енергетика і автоматика, 2016)
As the part of a systematic approach of the strategy implementation automated synthes is of robotic mechanical assembly technologies the formalization of the components of solvability conditions (SC) was proposed. There are parametric feasibility conditions (PFC). Maintenance of PFC tasks are defined and formalized the conditions of existence of the PFC. The set of PFC tasks is decomposed. As a result the parts define the following parameters: technological service of industrial robot of each working position of flexible manufacturing cell, among aggregate motions of gripper of stationary industrial robot between working positions and their coordination.